The critical intertwining of historicity: historicity as phenomenological and existential crisis in Merleau-Ponty’s works - Davis, Duane (Argumentos - Revista de Filosofia, 2023)
Merleau-Ponty’s account of historicity is significant both as a phenomenological account and as an existential account of our historical situation. Of course, these aspects of his work are not mutually exclusive, but intertwined. And each aspect contributes to the sense of crisis of human historicity. We will first consider the phenomenological crisis of historicity—which is to say, we will consider the crisis of historicity phenomenologically. This is the attempt to reveal the conditions of the possibility of history from within history or the structure of our historical situation—where Merleau-Ponty’s position departs from Husserlian phenomenology. Next, we will consider the existential crisis of historicity—which is to say, we will consider the crisis of historicity existentially. This is the attempt to understand the imperative that things matter to us historically. Finally, we will briefly indicate the importance of these aspects of our historicity as a critical intertwining. This critical intertwining reveals the mutual encroachment of the “how” and the “why” of our historicity, which Merleau-Ponty describes at the end of his career as chiasmic existence within the flesh of the world. The critical intertwining as interrogation of our historical being provides the "who" "what" "when" and "where" of our historicity.